2021
DOI: 10.1021/acssuschemeng.1c05051
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Oxygen Permeability in Chitin/Cellulose Nanomaterial Coatings by Tuning Chitin Deacetylation

Abstract: The demand for packaging materials with low gas permeabilities is increasing, but commonly used petroleum-derived single-use plastics are not renewable, biodegradable, or easy to recycle. Nanomaterials composed of chitin and cellulose, which are abundant in nature, have high crystallinities and low oxygen permeabilities (OPs), providing a viable alternative. In this work, we explore how deacetylation conditions of crab shell chitin can be used to tune the charge and size of the resulting chitin nanowhiskers (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 63 publications
4
39
0
Order By: Relevance
“…This OP is also lower than that of a spray-coated PLA-ChNF-CNC film from a previous study (∼20 cm 3 ·μm/m 2 /day/kPa with a 1-μm-thick coating layer), which is probably because of the much thicker coating layer in this work (i.e., 31 and 39 μm). Another possibility is that the ChNFs used in the aforementioned work were significantly longer than those in our work, i.e., several microns versus 118 ± 55 nm, and it has been found that shorter ChNFs may result in a lower OP because they pack more densely …”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…This OP is also lower than that of a spray-coated PLA-ChNF-CNC film from a previous study (∼20 cm 3 ·μm/m 2 /day/kPa with a 1-μm-thick coating layer), which is probably because of the much thicker coating layer in this work (i.e., 31 and 39 μm). Another possibility is that the ChNFs used in the aforementioned work were significantly longer than those in our work, i.e., several microns versus 118 ± 55 nm, and it has been found that shorter ChNFs may result in a lower OP because they pack more densely …”
Section: Resultsmentioning
confidence: 71%
“…This was repeated 10 times and averaged. The degree of acetylation (DA) of ChNF was determined by potentiometric titration using a pH meter (Seven Excellence S400, Mettler Toledo) . The ζ potential values of 0.025 wt % ChNF and 0.025 wt % CNC, which were diluted with pH = 3 HOAc solution and 5 mM NaCl solution at pH = 7, respectively, were measured by a Zetasizer Nano ZS (Malvern Panalytical, U.K.).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A 0.5 wt% ChNW suspension was obtained by deacetylating commercial chitin (Tidal Vision, USA) sourced from crustacean shells under the optimized conditions as previously reported, i.e., in a 40% sodium hydroxide (NaOH) solution heated with an oil bath at 155 1C for 140 min with a liquid-solid ratio of 25 : 1 (mL g À1 ), followed by high-pressure homogenization. 22 A 0.5 wt% CNC suspension was obtained by diluting a 10 wt% CNC slurry extracted from pulp provided by USDA Forest Products Laboratory, USA. The properties for CA, ChNW, and CNC are available in Tables S1, S2 and S3 (ESI †) respectively, and details about their characterizations are available in the ESI.…”
Section: Methodsmentioning
confidence: 99%